The psychological symptoms and behavioral problems of children with mothers working as medical staff in the crisis of Covid-19 outbreak in Hamadan, Iran - Raeisi, Roya; Gholamzad, Shakiba; Dehkordi, Mansoureh Kiani; Kheirabadi, Mehri Rezaei; Ddehkordi, Ali Hhasanpour; Sobhani, Mohammad Mahdi; Movahedi, Mahsa (Frontiers in Psychiatry, 2023)
Background and aim: The purpose of this study was to investigate the psychological symptoms and behavioral problems of children with mothers working as medical staff in the crisis of Covid-19 disease in Hamadan. Materials and Methods: This descriptive causal-comparative study was conducted on all mothers with children aged 6 to 12 years in Hamadan. In this study, eligible individuals were selected using simple random sampling, and were assigned to two groups of mothers working as the treatment staff and the control group. The research instruments included the Child Behavior Checklist (Achenbach) and the Child Symptom Inventory-4 (CSI-4). Results: The results showed that the mean scores of psychological and behavioral symptoms of children in terms of group membership (group of mothers working in the treatment staff and control group) had a significant difference. There was a significant difference between the mean scores of depression, attention problems and aggression in children in the staff group and the control group, which means that children in the staff group, depression, attention problems and aggression scored higher than children in the control group. There was no significant difference between the mean anxiety scores of the group of working mothers and the control group (p <0.05). Conclusion: Children whose mothers work as medical staff for Covid-19 show more depression, and attention and aggression problems than children whose mothers do not work medical staff.